Murine gammaherpesvirus 68 ORF20 induces cell-cycle arrest in G2 by inhibiting the Cdc2–cyclin B complex - Nascimento, R.; Parkhouse, R. M. E. (Journal of General Virology, 2007)
The objective of this work was to identify novel viral ‘evasion’ genes without homology in the database through functional assays. Using this approach, the ‘unassigned’, conserved murine gammaherpesvirus ORF20 gene was shown to localize in the nucleus and to induce cell-cycle arrest followed by apoptosis in both mouse and human cells. Such growth-arrested cells did not express phospho-histone H3, demonstrating that the virus protein caused arrest at the G2 stage of the cell cycle. To characterize the mechanism further, Western blots of ORF20-recombinant lentivirus-infected cells were developed with antibodies to cyclin B1, Cdc2 and phospho-Tyr-15-Cdc2. This analysis revealed a relative increase in cyclin B and phospho-Tyr-15-Cdc2, from 24 to 72 h after infection with recombinant lentivirus. The demonstration that Cdc2 is in its inactive phosphorylated form and the clearly increased levels of cyclin B indicated that the virus gene blocks the progression of cells into mitosis by acting at the level of the Cdc2–cyclin B complex. To confirm this result, the Cdc2–cyclin B complex in ORF20-expressing cells was shown to be essentially without kinase activity. As the ORF20 gene is conserved in all herpesvirus, it may be presumed to have evolved to fulfil an important, as yet undefined, biological role in host-cell modification.